If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -8 + 2x = 7 + -9 Reorder the terms: -8 + 4x + 2x = 7 + -9 Combine like terms: 4x + 2x = 6x -8 + 6x = 7 + -9 Combine like terms: 7 + -9 = -2 -8 + 6x = -2 Solving -8 + 6x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6x = -2 + 8 Combine like terms: -8 + 8 = 0 0 + 6x = -2 + 8 6x = -2 + 8 Combine like terms: -2 + 8 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| 4x+20=8x+12 | | 1.6x-1.8+x-2= | | 7x^3+7x^3= | | 6y=-15+5x | | V=(3.14) | | 2a^3-5a^2-2a^5= | | (8z)(-4z^5)= | | 81x^2-y^2=0 | | -x-16=5x+7-5 | | 324=2x+2y | | 4t+5t=0.5 | | 4t^2-25t-15=0 | | 2a+4=2a-4 | | 8-h*2h=72 | | n-6=23 | | 4y=-3x-16 | | 11+(2-1)-4= | | 3-121=-164 | | 2x^2-X-0=0 | | 15+u=50 | | 7*-1-3*-6=11 | | 9.69(s+w)=100 | | 11+(n-1)-4= | | 7*-2-3*7=11 | | 12h-5=11h+5-r | | 4n-7+n-1=2n+19 | | 45x-25x=0 | | 3p-7n=p | | 5+7b=-2 | | 7*5-3*8=11 | | y+3=5(x-7) | | 7*0-3*-4=11 |